PREDICTIVE PROGNOSTIC VALUE OF REVERSE SHOCK INDEX MULTIPLIED BY GLASGOW SCALE rSIG in trauma patients - LOUASSEF Fatima Amet Elrahman; BENANTEUR Aqila; MOUSSAOUI Wiam Nourhane (université ammar telidji laghouat, 2024)
Background: Trauma is one of the leading causes of death and disability around the world and it is one of the important issues in public health. In the field of emergency medicine, a careful evaluation of trauma severity is essential to steer clinical interventions and enhance patient outcomes. The Reverse Shock Index multiplied by Glasgow Scale (RSIG) holds promise as a potential prognostic tool for trauma patients. However, there is limited research examining its predictive efficacy in real-world clinical settings, particularly within the context of Colonel Lotfi Hospital. This study aims to externally validate the accuracy of the rSIG in the prediction of mortality, need for transfusion and need for surgical procedure Materials and methods: This is a retrospective, comparative, analytical cohort study, Data were collected from the medical records of hospitalized patients and operative protocols of Colonel Lotfi Mixed Hospital and Hmida Benadjila Hospital in Laghouat for severe trauma between January 2018 and December 2022, where the series focused on patients aged between 18 and 80 years who were hospitalized for severe trauma or polytrauma. The outcomes were circumstances of the trauma, vital signs (SBP, DBP, HR, RR) at ED presentation, GCS and hemoglobin levels at ED presentation, the need of transfusion and the need of surgical intervention, and the in-hospital mortality. Results:78 patients were admitted to the emergency department for severe trauma, the average age of our study population was close to 40 years old, with a male predominance (80.8%). Blunt trauma was the most frequent type of injury among our population with (94.9%) while chest trauma was the most site of injuries received in the emergency department (78.2%). The main mechanism of trauma was car accidents with a frequency of 34.6%. In these inferential analyses we compare two groups with many parameters in order to find which parameters have significant effect on the two groups, we found that rSIG, HB, need for transfusion, Damage control, some sites of injury like: traumatic brain injury, facial injury, cervical and pelvic injuries have significant impact on the mortality rate, we also found that the type of injury that has a significant impact on mortality is the penetrating trauma. the average of rSIG score among survivals was around 17.4, and its average among dead was 7.9 with a (P < 0.00*), another inferential analysis comparing group A (rSIG<15) and group B (rSIG>15) with different parameters that tend to have significant results which are Dead in hospital, need for transfusion, damage control, operated patients and re-operated patients. The frequency of in-hospital mortality was significantly higher in group A when compared to group B [51.2% versus 02.7%; P<0.00***]; in addition, around 80.5% from A group needed blood transfusion and only 21.6% from B group with a significant association (P <0.00**). 43.9% from A group had damage control and only 02.7% from B group with a significant association (P <0.00***). Conclusion: The Reverse shock index multiplied by GCS score is more accurately identifies patients with severe trauma at highest risk of death, massive transfusion and surgical procedure. These findings may help further refine early risk assessments for patient management, we recommend using it in our hospital and others healthcare structures, we also suggest to provide advance diagnostic tools in the hospital structures of Laghouat to prevent errors in the vital parameters.
cd-rom